Sishun Formula for acute migraine attack: study protocol for a double-blind, randomized, placebo-controlled trial - Zhang, Xuran; Liu, Jiaojiao; Li, Huanqin; Zhou, Bo; Wang, Shaoqing; Li, Lexi; Wu, Xuefeng; Cao, Kegang (Frontiers in Neurology, 2025)
PurposeMigraine, a leading global cause of disability, affects over 1.1 billion individuals worldwide. Current acute pharmacotherapy is limited by contraindications and adverse events (AEs), underscoring the need for safer, more effective alternatives. The Sishun Formula (SSF), a traditional Chinese medicine (TCM) formulation targeting “Ying-Wei disharmony,” demonstrated promising preclinical and preliminary clinical results. This trial aims to rigorously evaluate SSF’s efficacy and safety for acute migraine attacks.Patients and methodsThis multicenter, randomized, double-blind, placebo-controlled trial will enroll 144 participants with acute migraine and “Ying-Wei disharmony” syndrome, randomized 1:1 to SSF or placebo. A single dose of SSF or a matched placebo is administered within 0.5 h of migraine onset. The primary outcome is the proportion achieving headache freedom at 2 h post-dose. Secondary outcomes include the proportion achieving headache relief at 2 h post-dose, absence of most bothersome associated symptoms, sustained relief/freedom at 24/48 h, the Visual Analogue Scale (VAS) score changes, time to efficacy onset, recurrence rates, and TCM syndrome improvement. Biomarkers [e.g., calcitonin gene-related peptide (CGRP)] and safety parameters (vital signs, laboratory tests, AEs) are monitored. Data analysis will employ SPSS 25.0 and R 4.3.1.ConclusionThe findings are anticipated to deliver high-quality evidence validating SSF’s efficacy and safety, offering a promising therapeutic alternative for acute migraine attacks.Clinical trial registrationhttp://itmctr.ccebtcm.org.cn/, identifier ITMCTR2025000187.